Uma leitura política dos contos Rip Van Winkle (1819) e A lenda do cavaleiro sem cabeça (1820), de Washington Irving (1783-1859) - Prearo, Paula Aline (2023)
The objective of this master's thesis is to investigate the short stories Rip Van Winkle and The legend of Sleepy Hollow - The legend of the headless horseman -, by Washington Irving, from the perspective of dialectics, in other words, of sociological criticism, as postulated by the American theorist Fredric Jameson in The political unconscious (1992) and two other great exponents, who contribute to the delineation of the theoretical contribution of the analysis: the Brazilian literary critic Antonio Candido and Roberto Schwarz, active critic in the literary sphere. In this way, we seek to investigate, in a dialogue between literature and society, or between form and content, how the two tales mobilize, in their intrinsic organization of form, the idealization of the dream of American nation-building and its identity clashes in the face of various regional, cultural, economic, and political divisions that made up a precursor and original identity of the United States, beyond the children's reading attributed to the tales nowadays. The analysis is guided by the three interpretative levels proposed by Fredric Jameson, in which the first deals with the manifest content of the work - the text itself - and its proximity to the universe of literature for children, the second deals with the social problems that interpellate the tales, and the third expands semantically, through the ideology of the form, the interpretation of the tales as inherent parts of the construction of the history of the country, of the formation of the American nation, besides clarifying, through the form itself, the reasons why the tales are attributed the classification of children's literature.